Solving the manufacturing costing equation.
Contract manufacturers, job shops and OEMs bolster the bottom line with effective cost estimating methods. Some manufacturers use basic costing methods, such as Excel spreadsheets. Others use custom structured query language (SQL) relational databases. Then there are shop management production systems, ERP software, or even more specialized cost-estimating software packages. No matter the solution, understanding the full costs of a product is critical today.